The significance of bringing the absent in the text Quranic A study in the interpretation of balance (Journal of the College of Basic Education, 2023)
By (bringing the absent) I mean some of what the rhetoricists have studied in the chapter on paying attention.Arabic dictionaries indicate that (turnip) is a transitive verb by itself, with the meaning of: twist, 1, and from this sensual indicationThe immanent or metaphor came, so it is said: He turned him away from showing him, that is: turned him away from him, and the friend indicated2 While (turnip) and (felt) mean the same thing, while Ibn Faris indicated that “the blame and the fulfillment And the word “Taa’” is a single word denoting: to twist, to divert something from its straight direction.” 3From this linguistic meaning came the meaning